Generation of compressed air by cascaded thermocompressors – project status - Fischer Fabian (EDP Sciences, 2021)
Compressed air is one of the most widely used industrial energy sources, and its production by mechanical compressors is extremely expensive and, in addition, inefficient. Therefore, the utilization of waste heat, which accrues on a large scale in many industrial applications, by means of a thermocompressor is an obvious alternative. This contribution presents a design approach to experimentally investigate a reciprocating thermocompressor with a self-actuated overdriven free displacer. These experiments shall be the basis for the design and realization of a cascade of identical stages, which has so far only been investigated by means of analytical modelling and theoretical similarity considerations. The main advantage of this approach is its extreme constructive simplicity and the expected self-regulating effect, which both facilitate a cost-effective production and operation. As the minimization of dead volume and fluid friction losses is essential, the heat exchangers and the regenerator are plainly realized by an annular gap around the displacer in the proposed design, thus further increasing its simplicity. The design parameters are determined by an optimization based on an analytical model extended by various losses and heat transfer limitations.